Enteral nutrition versus parenteral nutrition after major abdominal surgery in patients with gastrointestinal cancer: a systematic review and meta-analysis. Issue 5 (25th April 2016) - Zhao, Xu-Fei; Wu, Ning; Zhao, Guo-Qiang; Liu, Jian-Fang; Dai, Ye-Feng
Abstract : To clarify the benefits of enteral nutrition (EN) versus total parenteral nutrition (TPN) in patients with gastrointestinal cancer who underwent major abdominal surgery. Medline, Cochrane, EMBASE, and Google Scholar were searched for studies published until July 10, 2015, reporting outcomes between the two types of postoperative nutritional support. Only randomized controlled trials (RCTs) were included. A χ 2 -based test of homogeneity was performed using Cochran's Q statistic and I 2 . A total of 2540 patients (1268 who received EN and 1272 who received TPN; average age range: 58.3–67.7 years) from 18 RCTs were included for assessment. Patients who received EN had shorter lengths of hospital stay (pooled difference in mean=−1.74, 95% CI −2.41 to −1.07, p<0.001, shorter time to flatus (pooled difference in mean=−1.27, 95% CI −1.69 to −0.85, p<0.001), and significantly greater increases in albumin levels (pooled difference in mean=−1.33, 95% CI −2.18 to −0.47, p=0.002) compared with those who received TPN after major abdominal surgery, based on a random-effects model of analysis. EN after major abdominal surgery provided better outcomes compared with TPN in patients with gastrointestinal cancer.